Pengembangan Lembar Kerja Peserta Didik Berbasis High Order Thinking Skill Pada Materi Usaha Dan Energi - Noviana Dara; Antonius Suban Hali; Aurelia Astria L. Jewaru; I Wayan Sukarjita (UNIB Press, 2026)
This study aims to develop a Student Worksheet (LKPD) based on the High Order Thinking Skill (HOTS) approach on the topic of Work and Energy, and to determine the validity and practicality of the developed LKPD. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects were eleventh-grade science students at SMA Negeri 1 Hawu Mehara. The instruments used in this study included validation sheets from material experts and LKPD experts, as well as questionnaires to collect responses from teachers and students. The validation results showed that the HOTS-based LKPD was categorized as valid, with a score of 80% from material experts and 71% from LKPD experts. The LKPD was also declared practical by teachers and students, as indicated by the small-group trial result of 87%, the large-group trial result of 89%, and teacher responses reaching 98%. The collected data were analyzed descriptively and quantitatively using a rating scale to determine the levels of validity and practicality of the product. The LKPD has several advantages, including its connection of the material to real-life situations, attractive presentation, and ability to make students more active and interested in learning physics. Therefore, the HOTS-based LKPD on the topic of Work and Energy is highly feasible to be used as a teaching material in physics learning to support students’ higher-order thinking skills.